PERANAN KOMPETENSI SOSIAL PADA TINGKAH LAKU KOPING REMAJA AKHIR - Fasikhah, Siti Suminarti (Universitas Muhammadiyah Surakarta, 1995)
Social competence is a from of social skill that can be learned and developed to increase the quality of adolescents coping behavior since sosial competence is the index and predictor for the adolescent healthy adjustment. The purpose of this study was to investigate the role of social competence on the late adolescents coping behavior. The subjects of this study were late adolescents who were student of the third grade of SMA Batik I, SMA AL Islam I and SMA Muhammadiyah I in Surakarta. They were between 18-21 years of age. The instrumens used to collect the data were social competence and coping behavior scales. The social competence scale was based on four aspects: (a) social knowledge, (b) self confidence, (c) empathy and (d) social sensivity. The coping behavior scales was categorized into two factors: (a) mature coping behavior and (b) immature coping behavior. The statistical methods to analyze the data were intercorrelation matrix analysis and simultan regression analysis. The results of this study were as follow: (a) the level of social competence has a role on the quality of adolenscents coping behavior, (b) sensivity aspects contributed most to the immature coping behavior.